Rethinking Cairo’s elevated urban highways: Scoping impacts and potentials - Dessouky, Nermin (AUC Knowledge Fountain, 2016)
Urban policies of the last 50 years in Egypt focused on extending and developing road networks to the extent that Egyptians used to describe it as the era of roads and bridges. From such policy came an introduction of a big number of elevated urban highways that cuts through Cairo’s urban fabric to ensure the flow of the city. Elevated urban highways are often perceived as a tool for mobility, but it introduces much more complicated impacts on the urban fabric and the communities that they pass through. While the international literature has long pointed out such impacts there is a gap in the local Egyptian literature that discusses the notion of elevated urban highways and its various impacts. It is argued that highways introduce a set of social, environmental and economic impacts, but most importantly some of those impacts are actual potentials that can be utilized to serve the needs of the community. This research aims at scoping the impacts and potentials of Cairo’s elevated urban highways. Understanding the impacts and potentials will provide better information for decision-making leading to better urban management of affected areas. This is achieved through studying three independent cases of elevated urban highways in Cairo: Al Azhar bridge, 15th of May bridge, and Saft El-Laban corridor. Through site visits and in-depth interviews with local stakeholders, the research provides an understanding of how the presence of elevated structure impacted each community, analyzes its spatial elements and scopes its potential uses. Based on the observations and investigations, many findings were revealed, like how communities perceive elevated highways differently, and how a negative impact in one case can actually be perceived as a positive impact in another case. Empirical findings presented interesting observations that sometimes contradict with the international literature and theories. The field work lead to realizing how new structures can lead to the formation of different power dynamics related to claiming ownership in each case. Observations and research reflected how the laws and regulations in regards to spaces under the elevated highways are vague, leading to misunderstandings and conflicts in regards to ownership and uses. Most importantly discussions reveal that Cairo’s elevated urban highway holds much more spatial potentials than the common belief of being just a tool for mobility.